Endoscopic and Microscopic Transsphenoidal Surgery of Craniopharyngiomas: A Systematic Review of Surgical Outcomes Over Two Decades - Cagnazzo, Federico; Zoli, Matteo; Mazzatenta, Diego; Gompel, Jamie J. Van (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Objective Few studies have compared transsphenoidal endoscopic (TE) and transsphenoidal microscopic (TM) techniques for the treatment of craniopharyngiomas.Design We performed a systematic review of published series. The results were stratified in two time periods from 1995 to 2016.Results A total of 48 articles and 1,186 patients met the inclusion criteria. Overall, 60% of endoscopic cases were supradiaphragmatic, and 76% of microsurgical cases were infradiaphragmatic. Mean tumor size was 3 cm and 2.4 cm in the TE and TM series, respectively (p = 0.008). Total resection rate was similar (66%) between TE and TM. Considering the surgical outcome for different tumor locations, total resection rate was slightly higher in the TE for supradiaphragmatic lesions (59% versus 42.5%; p = 0.26). Recurrence rate was higher in the endoscopic series (21.7% versus 12%). Mortality and the overall complication rates were similar (p = 0.84). However, hydrocephalus (7.6%) and cognitive dysfunction (15.8%) were more common in TE, and meningitis (6%) and endocrinologic complications were more common in the TM series. In the past 6 years, the rate of cerebrospinal fluid leak in TE was significantly lower (13%) and was comparable between TE and TM.Conclusion Both techniques appear comparable for infradiaphragmatic lesions; however, TE seems to yield better results for supradiaphragmatic tumors. In conclusion, more complex lesions with difficult locations can be effectively treated with endoscopic surgery.
Keywords: craniopharyngioma; endoscopic; microsurgical resection; transsphenoidal